Implementación de procedimientos operativos estandarizados y de saneamiento al alimento balanceado para cerdo en los Talleres de la ESPAM MFL - Reinoso Zambrano, Gema Estefanía (2018)
The present research work was based on the implementation of standardized operating procedures and sanitation (POES), in the flour and balance workshop of the MFL ESPAM to control the safety of the same. for which a descriptive investigation was carried out that allowed to diagnose a before and after of said implementation. The initial diagnosis through an observation card that showed a breach of good manufacturing practices (BPM) by 65%, and with a 35% compliance; Five initial balancing samples were taken to verify if the product meets the microbiological requirements established in the INEN 1829 standard, the results evidenced the presence of Enterobacteriaceae, molds and yeasts; According to the Pareto diagram, the causes that generate the presence of these microorganisms are due to the inadequate cleaning and disinfection process in equipment and utensils, lack of operating procedures, inadequate storage of raw materials and personnel hygiene. During the implementation, personnel training was carried out, records were prepared to organize and control the planning in the preparation of the balance. After the implementation, 76% compliance was demonstrated, and 24% of a non-compliance of BPM in all the areas evaluated, and through laboratory analysis it was determined that the number of samples contaminated by Enterobacteriaceae, molds and yeasts was obtained. the same, arriving at the conclusion that the implementation of POES and POE benefits the microbiological innocuity.